Konfigurasi Arduino IDE Untuk Monitoring Pendeteksi Suhu dan Kelembapan Pada Ruang Data Center Menggunakan Sensor DHT11 - Hakiki, M Irsyad; Darusalam, Ucuk; Nathasia, Novi Dian (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
In this Digital era, Microcontrollers are now growing rapidly and are increasingly in demand in control system applications. Including Arduino Microcontroller, by using this Arduino trying to overcome a problem that often occurs in the Data Center space, namely the problem of temperature and humidity instability that has a major impact on data on each rack in the data center space. This problem occurs if the temperature is too hot or too excessive humidity which results in overheating so that it can damage data stored in the data center. To solve the problem, Arduino detects temperature and humidity using a DHT11 module that can detect clearly and accurately, and can display on the LCD screen, or display the results of temperature and humidity detection on a webbased Thingspeak application and the Blynk application that can be accessed via a smartphone. Internet-based of Things (IoT). With DHT11 processed by Arduino can produce an ideal temperature of 18 ° C - 28 ° C and humidity of 40.00% - 60.00%, and provide Notifications that will be sent to the blynk application if there are problems with temperature and humidity instability.